SEISMIC PICTURE OF A FAULT ZONE. WHAT CAN BE GAINED FROM THE ANALYSIS OF FINE PATTERNS OF SPATIAL DISTRIBUTION OF WEAK EARTHQUAKE CENTERS? - Gevorg G. Kocharyan; Svetlana B. Kishkina; Aleksey A. Ostapchuk (Геодинамика и тектонофизика)
Association of earthquake hypocenters with fault zones appears more pronounced in cases with more accurately determined positions of the earthquakes. For complex, branched structures of major fault zones, it is assumed that some of the earthquakes occur at feathering fractures of smaller scale.It is thus possible to develop a «seismological» criterion for definition of a zone of dynamic influence of faults, i.e. the zone containing the majority of earthquakes associated with the fault zone under consideration.In this publication, seismogenic structures of several fault zones located in the San-Andreas fault system are reviewed. Based on the data from a very dense network of digital seismic stations installed in this region and with application of modern data processing methods, differential coordinates of microearthquakes can be determined with errors of about first dozens of meters.It is thus possible to precisely detect boundaries of the areas wherein active deformation processes occur and to reveal spatial patterns of seismic event localization.In our analyses, data from the most comprehensive seismic catalog were used. The catalogue includes information on events which occurred and were registered in North California in the period between January 1984 and May 2003. In this publication, the seismic data processing results and regularities revealed during the analyses are compared with the data obtained from studies of fault structures, modeling and numerical simulation results. Results of quantitative research of regularities of localization of seismic sources inside fault zones are presented.It is demonstrated by 3D models that seismic events are localized in the vicinity of an almost plain surface with a nearly constant angle of dip, the majority of events being concentrated at that conventional surface.Detection of typical scopes of seismicity localization may prove critical for solution of problems of technogenic impact on fault zones for the purpose of partial stress release. The obtained results suggest that the region, wherein active deformation takes place during preparation of medium earthquakes (M≤6.5÷7.0), includes a number of local «strips», each about 100 m in width. The latter size is comparable to a scope of technogenic capabilities of producing an impact on geo-environment. It is hoped that studies of both fine spatial and temporal patterns of seismicity in the vicinity of fault zones will allow to find reliable pinpoints for definition of both place and time for implementation of technogenic impacts.In our opinion, the implemented study demonstrates the burning need to establish test sites with dense and wellequipped local seismic networks in Russia.